The pocket universal methods of design : 100 ways to research complex problems, develop innovative ideas and design effective solutions - Martin, Bella; Hanington, Bruce (Rockport Publishers, 2018)
The ultimate handbook for designers, students, and even educators, this pocket edition is armed with 100 principles of design knowledge to keep your team sharp.